Spectrum of ɮ-genemutations in patients diagnosed in UKMMC / Khairiliah Ausikhin Khairuman - Khairuman, Khairiliah Ausikhin (2015)
ɮ -thalassemia and HbE are autosomal recessive disorders that affect the synthesis of Pglobin gene. These defects mainly caused by point mutations on chromosome 11. Due to the multi-ethnicity of Malaysia, each ethnic population has its own common mutation. The aim of this study was to characterize p-globin gene mutation present in Malay and Chinese patients of UKMMC using multiplex ARMS polymerase chain reaction (MARMS-PCR). Initially, 120 samples were selected based on presence of hypochromic microcytic red blood cells and raised HbA2, HbF, HbE and Hb Variant. Presences of the different types of mutation were then tested by using ten primers of common P-globin gene mutations using MARMS-PCR. Once the mutation was detected, heterozygosity and homozygosity of the mutation was identified. Out·of the 120 samples, 80 samples were detected with increase HbA2, HbF, HbE and Hb Variant. MARMS-PCR managed to detect 75 samples with mutation while another 5 were uncharacterized. It was also found that 52% from the sample were HbE patients with positive for CD26(G-A). As for the group of p-thalassemia it was noted that the most common p-thalassemia mutation were CD41/42(36.l%), followed by IVSl-5(G-C)(33.3%). Among the Malay patients, HbE and IVS 1-5 were the most common mutation seen whereas CD41/42 was most common among the Chinese. Genotyping result showed all HbE and 33 of the 13thalassemia samples were heterozygotes. Only 3 samples were homozygotes which all from IVSl-5. Hence the study managed to provide the pattern of p-gene mutations for the two main ethnics in Malaysia.